Allergic sensitization and obstructive airway diseases among an adult rural population in Nepal - Drews, Arne; Lama, Poonam; Nepal, Niraj; Joshi, Rajesh Dhoj; Gran, Anja; Schreiber, Jens (Nepalese Respiratory Journal, 2022)
Background: The relevance of the obstructive lung diseases asthma and COPD and IgE-mediated allergy in Nepal is still poorly characterized. Method: In a cross-sectional study in rural Nepal 199 persons were characterized with a questionnaire, skin prick tests, spirometry and total IgE concentration in serum. Results: About 20% of the women and 50% of the men were current smokers. Half of the study population used biomass fuel at home to cook or to heat and 70% of the study participants experienced dust-exposure at work or at home. 50% of the women and 30% of the men had a history of COPD, while 57% of the women and 53% of the men had symptoms of respiratory allergy. 18% of the women and 16% of the men used inhaler devices. 62% of the women and 66% of the men had a total IgE concentration in serum >100 IU/mL. About 30% of the women had a FEV1 < 80% and about 10 % had a FEV1 < 40%, also 30% of the men had a FEV1 <80% but none of the men had a FEV1 <40%. The FEV1/VC ratio was smaller than 70% in 13 % of the women and 14,6% of the men. We observed a significant inverse correlation between serum IgE with FEV1. 14% of study participants had positive prick test for house dust mite, 5% were positive for cat dander and 3% were positive for mugwort. Conclusion: In summary this study shows an relevant burden of obstructive pulmonary disorders and IgE-mediated allergy in a rural Nepalese population.